The Effect of Financial Ratios on Financial Distress During the Covid 19 Period: Pengaruh Rasio Keuangan Terhadap Financial Distress Pada Masa Covid 19 - Helena Kournikova; Nurasik Nurasik (Universitas Muhammadiyah Sidoarjo, 2021)
The purpose of this study is to determine, analyze, and explain the significant influence between the variables of Liquidity, Profitability, Leverage, Activity and operating cash flow on financial distress in Transportation Sub-Sector Companies listed on the Indonesia Stock Exchange for the second Quarter of 2020, namely as many as 36 million companies. This research uses a quantitative approach. By using secondary data from the IDX official website. Data collection is done by tracing financial statements, annual reports and previous journals. The analysis technique used in this research is multiple regression analysis technique. Liquidity, profitability, and cash flow have a significant effect on Financial Distress, while Leverage and Activity have no significant effect on Financial Distress.